Outcomes of critically ill COVID-19 patients managed in a high-volume severe respiratory failure and ECMO centre in the United Kingdom. (May 2022) - Sherren, Peter B; Camporota, Luigi; Sanderson, Barnaby; Jones, Andrew; Shankar-Hari, Manu; Meadows, Chris IS; Barrett, Nicholas; Ostermann, Marlies; Hart, Nicholas
During the Coronavirus Disease 2019 (COVID-19) pandemic institutions have needed to develop pragmatic clinical pathways to balance the excess critical care demand and local resources. In this single-centre retrospective cohort study we describe the outcomes of COVID-19 patients admitted to Guy's and St. Thomas' NHS Foundation Trust (GSTT) critical care service. Patients were managed according to a local respiratory failure management pathway that was predicated on timely invasive ventilation when indicated and tailored ventilatory strategies according to pulmonary mechanics. Between 2 March and 25 May 2020 GSTT critical care service admitted 316 patients with confirmed COVID-19. Of the 201 patients admitted directly through the Emergency Department (ED) with a completed critical care outcome, 71.1% survived to critical care discharge. These favourable outcomes may serve to inform the wider debate on optimal organ support in COVID-19.